2007
DOI: 10.1108/01443570710750286
|View full text |Cite
|
Sign up to set email alerts
|

The strategic influence of structural manufacturing decisions

Abstract: PurposeThe purpose of this study is to examine the relationship between the implementation of certain structural manufacturing decisions and the importance that is attached to certain competitive priorities in the firm's business strategy. The paper seeks to analyse the role these decisions play in the creation of a firm's competitive advantage, and aims to provide evidence of which decisions provide the firm with strategically relevant production capabilities.Design/methodology/approachThe hypotheses were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…As a matter of fact, our reliability test procedure is completely followed the methods of Chin (1998) to conclude the reliability of our measurement model. Moreover, we also notice that a few prior studies (e.g., Cousins, 2005;Oltra and Flor, 2010;Urgal-Gonzalez and Garcia-Vazquez, 2007), using covariance-based SEM techniques like LISREL, reported less than the desired reliability test results suggested in Nunnally (1978).…”
Section: Unlike Covariance-based Structural Equation Modelling Pls Dmentioning
confidence: 59%
“…As a matter of fact, our reliability test procedure is completely followed the methods of Chin (1998) to conclude the reliability of our measurement model. Moreover, we also notice that a few prior studies (e.g., Cousins, 2005;Oltra and Flor, 2010;Urgal-Gonzalez and Garcia-Vazquez, 2007), using covariance-based SEM techniques like LISREL, reported less than the desired reliability test results suggested in Nunnally (1978).…”
Section: Unlike Covariance-based Structural Equation Modelling Pls Dmentioning
confidence: 59%
“…There is significant strategic importance attached to how these manufacturing capabilities are developed. Urgal-Gonzalez and Garcia-Vazquez (2007) suggest that relationships exist between structural decisions and capabilities. Their study highlights the importance of structural decisions in enabling firms to acquire manufacturing capabilities.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Some studies in the industrial sector have shown the relationship between competitive priorities and infrastructural and structural decisions (Miller and Roth 1994; Acur et al Christiansen et al 2003;Urgal-González and García-Vázquez 2007). Christiansen et al (2003) suggest that certain practices, such as total quality management, human resources management and maintenance, positively influence competitive priorities.…”
Section: Relationships Between Operations Decisions and Competitive Pmentioning
confidence: 97%
“…Service organizations have many problems and challenges that can be addressed through operations management (Wright and Mechling 2002). Operations strategy is not limited to studying processes for providing a hotel service; it can also make a strategic contribution to generating sustainable competitive advantages (Urgal-González and García-Vázquez 2007). Operations strategy is defined as a long-term plan that includes the set of structural and infrastructural policies and decisions that must be made in order to achieve the organization's competitive strategy (Diaz-Garrido et al 2007).…”
Section: Introductionmentioning
confidence: 99%